Enhancing stroke risk prediction in patients with transient ischemic attack: insights from a prospective cohort study implementing fast-track care - Barone, Valentina; Foschi, Matteo; Pavolucci, Lucia; Rondelli, Francesca; Rinaldi, Rita; Nicodemo, Marianna; D’Angelo, Roberto; Favaretto, Elisabetta; Brusi, Carlotta; Cosmi, Benilde; Degli Esposti, Daniela; D’Addato, Sergio; et al. (Frontiers in Neurology, 2024)
Background and aims Fast-track care have been proved to reduce the short-term risk of stroke after transient ischemic attack (TIA). We aimed to investigate stroke risk and to characterize short- and long-term stroke predictors in a large cohort of TIA patients undergoing fast-track management. Methods Prospective study, enrolling consecutive TIA patients admitted to a Northern Italy emergency department from August 2010 to December 2017. All patients underwent fast-track care within 24 h of admission. The primary outcome was defined as the first stroke recurrence at 90 days, 12 and 60 months after TIA. Stroke incidence with 95% confidence interval (CI) at each timepoint was calculated using Poisson regression. Predictors of stroke recurrence were evaluated with Cox regression analysis. The number needed to treat (NNT) of fast-track care in preventing 90-day stroke recurrence in respect to the estimates based on baseline ABCD2 score was also calculated. Results We enrolled 1,035 patients (54.2% males). Stroke incidence was low throughout the follow-up with rates of 2.2% [95% CI 1.4–3.3%] at 90 days, 2.9% [95% CI 1.9–4.2%] at 12 months and 7.1% [95% CI 5.4–9.0%] at 60 months. Multiple TIA, speech disturbances and presence of ischemic lesion at neuroimaging predicted stroke recurrence at each timepoint. Male sex and increasing age predicted 90-day and 60-month stroke risk, respectively. Hypertension was associated with higher 12-month and 60-month stroke risk. No specific TIA etiology predicted higher stroke risk throughout the follow-up. The NNT for fast-track care in preventing 90-day stroke was 14.5 [95% CI 11.3–20.4] in the overall cohort and 6.8 [95% CI 4.6–13.5] in patients with baseline ABCD2 of 6 to 7. Conclusion Our findings support the effectiveness of fast-track care in preventing both short- and long-term stroke recurrence after TIA. Particular effort should be made to identify and monitor patients with baseline predictors of higher stroke risk, which may vary according to follow-up duration.